An approach to assessing immunoglobulin dependence in chronic inflammatory demyelinating inflammatory polyneuropathy. Issue 4 (20th October 2021) - Kapoor, Mahima; Compton, Laura; Rossor, Alex; Hutton, Elsbeth; Manji, Hadi; Lunn, Mike; Reilly, Mary; Carr, Aisling
Abstract: Regular immunoglobulin treatment maintains strength and prevents disability in chronic inflammatory demyelinating polyneuropathy (CIDP). Discrimination between active disease, with optimum symptom control on treatment, and disease in remission not requiring treatment is essential for therapeutic decision‐making and clinical trial design. To compare treatment cessation versus gradual dose reduction in assessment of disease activity (immunoglobulin dependence) in a cohort of stable CIDP patients on maintenance immunoglobulin treatment. An approach to restabilization of immunoglobulin‐dependent individuals is also described. Retrospective review of IVIg cessation or gradual reduction in 33 patients with stable CIDP on maintenance IVIg. Demographic, clinical and treatment data were collected; clinical monitoring data were recorded prospectively as part of routine clinical practice. A total of 21/33 patients (62.6%) were immunoglobulin dependent, (gradual dose reduction:11, cessation:10). Mean change in Inflammatory Rasch‐built Overall Disability Scale (I‐RODS) (−15, standard deviation [SD] 16) and Medical Research Council Sum Score (MRC‐SS) (−4, SD: 4) was clinically and statistically meaningful (>75% exceeded minimum clinically important differences). Mean time to deterioration was 5.0 (SD: 4.6) months, shorter in cessation group (3.5 months) than gradual reduction group (8.8 months). All patients were restabilized to previous baseline (M: 2.3, SD: 4.3 months), half within 1 week of retreatment. A total of 12 patients (37.4%) remained stable without treatment for ≥2 years (remission). A total of 50% were identified rapidly by cessation and 50% by gradual dose reduction requiring mean 4.8 (SD: 2.8) years follow‐up and costing £113 623 per person Ig spend. No predictors of disease activity were identified. A treatment cessation trial with close clinical monitoring is an efficient, cost‐effective and safe approach to assessing disease activity in CIDP.